Posterior Quadratus Lumborum Block or Thoracolumbar Interfascial Plane Block and Postoperative Analgesia after Spinal Surgery: A Randomized Controlled Trial - Şenay Canikli Adıgüzel (17823365) (2023)
Introduction The management of postoperative pain following lumbar disc herniation (LDH) surgery is crucial for the quality of recovery. The effectiveness of multimodal analgesia plans increases when interfascial plane blocks are included. This study sought to compare the analgesic efficacy of preoperative ultrasound-guided TLIP (thoracolumbar interfascial plane) blocks and posterior QLBs (quadratus lumborum blocks) in patients undergoing LDH surgery. Methods Patients undergoing elective LDH surgery under general anesthesia were randomized into two groups: thoracolumbar interfascial plane block (Group T) and posterior quadratus lumborum block (Group Q). Block applications were performed 30 min before anesthesia induction. In the postoperative period, analgesia control was provided with a patient-controlled analgesia device. The patients’ 24 h cumulative opioid consumption was examined. Pain scores were evaluated in the 0th, 3rd, 6th, 9th, 12th, and 24th hours. Results The mean 24 h cumulative morphine consumption for patients was statistically insignificant when Groups T and Q were compared (9.14 ± 7.03 mg vs. 8.66 ± 6.58 mg, p = 0.788). Pain scores at rest and during movement as well as morphine consumption were similar between groups in the 0th, 3rd, 6th, 9th, 12th, and 24th hours (p > 0.05). Conclusions The study determined that the utilization of TLIP blocks and posterior QLBs prior to anesthesia induction yielded comparable outcomes in terms of reducing postoperative analgesic consumption and enhancing the efficacy of multimodal analgesia in individuals undergoing single-distance lumbosacral spine surgery under general anesthesia. Other Information Published in: Journal of Clinical Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/jcm12237217